Information Technology Architecture and Employee Innovation Performance in Iraqi University Libraries - Aladilee, Dr.Omaima Hameed Aladilee (Indonesian Journal of Law and Economics Review, 2026)
General Background: University libraries operate in dynamic knowledge environments that require technological systems capable of supporting information services and organisational activities. Specific Background: Information technology architecture, including hardware and equipment, software and databases, communications networks, and human resources, provides a framework that supports employees in performing their tasks and generating innovative ideas. Knowledge Gap: Empirical research integrating information technology architecture and employee innovation performance in the context of Iraqi university libraries remains limited. Aims: This study examines the relationship between information technology architecture and employee innovation performance in the libraries of the University of Karbala. Results: Using survey data from 87 employees and structural equation modelling analysis, the findings show a statistically significant relationship between information technology architecture and employee innovation performance (β = 0.796, p < 0.001), explaining 68.6% of the variance in innovation performance. Novelty: The study integrates multiple dimensions of information technology architecture with indicators of employee innovation performance within the organisational context of university libraries. Implications: The findings indicate that strengthening technological resources, communication networks, software systems, and staff development is associated with improved innovative work practices in knowledge institutions. Highlights: • Information Technology Architecture Dimensions Show Significant Relationships With Employee Innovative Capabilities. • Structural Equation Modelling Explains 68.6 Percent of Innovation Performance Variance in Libraries. • Technological Resources and Staff Development Support Creative Work Practices in Knowledge Institution. Keywords: Information Technology Architecture, Employee Innovation Performance, University Libraries, Information Systems Infrastructure, Organizational Innovation.